Binding Strength of Gram-Positive Bacterial Adhesins - Dufrêne, Yves F.; Viljoen, Albertus (Frontiers in Microbiology, 2020)
Bacterial pathogens are equipped with specialized surface-exposed proteins that bind strongly to ligands on host tissues and biomaterials. These adhesins play critical roles during infection, especially during the early step of adhesion where the cells are exposed to physical stress. Recent single-molecule experiments have shown that staphylococci interact with their ligands through a wide diversity of mechanosensitive molecular mechanisms. Adhesin-ligand interactions are activated by tensile force and can be ten times stronger than classical non-covalent biological bonds. Overall these studies demonstrate that Gram-positive adhesins feature unusual stress-dependent molecular interactions, which play essential roles during bacterial colonization and dissemination. With an increasing prevalence of multidrug resistant infections caused by Staphylococcus aureus and Staphylococcus epidermidis chemotherapeutic targeting of adhesins offers an innovative alternative to antibiotics.